Medical Text Classification Using Convolutional Neural Networks - Hughes, Mark; Li, Irene; Kotoulas, Spyros; Suzumura, Toyotaro (Studies in health technology and informatics, 2017)
We present an approach to automatically classify clinical text at a sentence level. We are using deep convolutional neural networks to represent complex features. We train the network on a dataset providing a broad categorization of health information. Through a detailed evaluation, we demonstrate that our method outperforms several approaches widely used in natural language processing tasks by about 15%.